Misregulation of the proline rich homeodomain (PRH/HHEX) protein in cancer cells and its consequences for tumour growth and invasion. Issue 1 (December 2016) - Gaston, Kevin; Tsitsilianos, Maria-Angela; Wadey, Kerry; Jayaraman, Padma-Sheela
Abstract The proline rich homeodomain protein (PRH), also known as haematopoietically expressed homeobox (HHEX), is an essential transcription factor in embryonic development and in the adult. The PRH protein forms oligomeric complexes that bind to tandemly repeated PRH recognition sequences within or at a distance from PRH-target genes and recruit a variety of PRH-interacting proteins. PRH can also bind to other transcription factors and co-regulate specific target genes either directly through DNA binding, or indirectly through effects on the activity of its partner proteins. In addition, like some other homeodomain proteins, PRH can regulate the translation of specific mRNAs. Altered PRH expression and altered PRH intracellular localisation, are associated with breast cancer, liver cancer and thyroid cancer and some subtypes of leukaemia. This is consistent with the involvement of multiple PRH-interacting proteins, including the oncoprotein c-Myc, translation initiation factor 4E (eIF4E), and the promyelocytic leukaemia protein (PML), in the control of cell proliferation and cell survival. Similarly, multiple PRH target genes, including the genes encoding vascular endothelial growth factor (VEGF), VEGF receptors, Endoglin, and Goosecoid, are known to be important in the control of cell proliferation and cell survival and/or the regulation of cell migration and invasion. In this review, we summarise the evidence that implicates PRH in tumourigenesis and we review the data that suggests PRH levels could be useful in cancer prognosis and in the choice of treatment options.